Pendidikan Agama Kristen Di Era Skeptisisme Digital: Rekonstruksi Pedagogi Iman Berdasarkan Teologi Kontekstual Timothy Keller - Sokhiziduhu Ndruru (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2025)
The era of digital skepticism has transformed how young people understand truth, authority, and identity, creating new challenges for Christian Religious Education (CRE). This study aims to analyze the contribution of Timothy Keller’s contextual theology in reconstructing a faith pedagogy that is relevant to the needs of the digital generation. The research employs a qualitative method with a library research approach through the analysis of Keller’s major works and scholarly literature related to Christian education, digital culture, and faith formation. The findings reveal that Keller’s ideas on contextual apologetics, the dialogue between faith and culture, and the integration of faith and life provide a strong foundation for developing a dialogical, contextual, and transformative faith pedagogy. Based on these findings, this study proposes a pedagogical model that encourages students to think critically, connect biblical teachings with digital realities, and embody Christian values in both personal and social life. This model is expected to strengthen the relevance of Christian Religious Education in nurturing a generation characterized by reflective faith, Christian character, and social responsibility in the digital age.